Teachers Evaluation Methods in Medical Education: Round Views of Faculty Members and Educational Experts: - Bastani, Peivand; Vatankhah, Soudabeh; TaherNejad, Ali; Ghasemi, Afsaneh (Galen Medical Journal, 2017)
Background: Since there is no agreement on the best approach of teachersâ€™ evaluation, this study was conducted to determine medical teachersâ€™ evaluation methods and clarify the viewpoints of Iranian faculty members toward them. Materials and Methods: A mix method study was conducted in two phases, systematic review and survey, in Tehran University of Medical Sciences on 400 faculty members. In phase one, 24 studies were analyzed among 1520 and based on that, the viewpoints of faculty members about 14 methods were assessed through a validated questionnaire. Independent t-test and one-way ANOVA were used for data analysis. Results: The participantsâ€™ age mean was 48.62+5.23 and most of them were assistant professors (121/36.01%). About 280 participants (83.3%) chose â€œmixed method ratingâ€ as the best way of evaluation; 68.7% of the participants though â€œstudent ratingâ€ cannot be an appropriate indicative for evaluating teachersâ€™ performance. The findings indicated statistical relationships between the average of some evaluation methods (student rating, peer evaluation, self-ratings, teaching scholarship, teaching awards) and the faculty membersâ€™ gender (P<0.05). There was also a significant relationship in average of student rating, peer evaluation, mentorâ€™s advice and self-ratings with participantsâ€™ age (P<0.05). Conclusion: None of the evaluation methods can be sufficient to show a correct status of teachersâ€™ performance. It is obvious that mix method evaluation as a combination of different measures and methods can be considered as a comprehensive approach; it is recommended to be applied in this university, and then compare teachersâ€™ satisfaction and performance before and after this transition.Â [GMJ.2017;6(3):233-239] DOI:10.22086/gmj.v0i0.725